Dismantling the Blueprint: Buurtzorg in English child protection social work. Issue 6 (2nd November 2021) - Hanley, Joe; McGrath-Brookes, Michael; Higgins, Martyn
ABSTRACT: November 2019 saw the release of A Blueprint for Children's Social Care (hereafter the Blueprint) in England. The Blueprint proposes introducing the Buurtzorg model of community nursing into the child protection social work in England, and received widespread interest and publicity. Buurtzorg is a Dutch community nursing agency that is based on a specific model of small self-managing and non-hierarchal teams. The authors of the Blueprint suggest that rapid and large-scale introduction of Buurtzorg into child protection social work would overcome many of the longstanding issues facing the profession in England. However, there are serious limitations to the suggestions outlined in the Blueprint and the Buurtzorg model does not translate well to child protection social work in England. Drawing on the work of Mark Fisher, this article examines the Blueprint under three core themes: consent and consensus, links with other neoliberal projects and failing forward. Ultimately, it is shown that the Blueprint can be considered part of a wider project of implementing neoliberal policies and market solutions to children's social care in England, a process that is increasingly being led by large, profit-driven global consultancy firms.